Development of Information Technology, Business Innovation, and Organizational Models Based on Local Wisdom in Improving MSME Performance (Case Study of Kuningan Regency MSME Actors - Gunawan, Wely Hadi; Masruroh, Rina; Nur Komarudin, Munir (Indonesian Journal Of Business And Economics, 2024)
This research aims to analyze the influence of information technology development, business innovation, and local wisdom-based organizational models on the performance of MSMEs in Kuningan Regency. MSMEs have a strategic role in Indonesia's economic development, especially in terms of contribution to GDP and employment. However, challenges such as low digital literacy, limited infrastructure and minimal use of technology often hinder the competitiveness of MSMEs. In this context, the integration of modern technology with local wisdom is a relevant approach to improving the performance of MSMEs. This research uses a quantitative approach with the Structural Equation Modeling (SEM) method to analyze the relationship between the variables studied. The research results show that business innovation has a significant influence on organizational models, while information technology development does not have a significant influence on organizational models or MSME performance. On the other hand, an organizational model based on local wisdom has been proven to significantly improve the performance of MSMEs. It is hoped that this research can provide practical and theoretical contributions, especially in supporting the development of competitive and sustainable MSMEs through the application of information technology, innovation based on local wisdom, and adaptive organizational models. Strategic recommendations include increasing digital literacy, business innovation training, and strengthening collaboration between MSMEs and other stakeholders. Keywords: Information Technology, Business Innovation, Organizational Model, MSME Performance